Eliciting willingness-to-pay through multiple experimental procedures: Evidence from lab-in-the-field in rural Ghana - Banerji, Abhijit; Chowdhury, Shyamal; De Groote, Hugo; Meenakshi, J.V.; Haleegoah, Joyce; Ewool, Manfred (Wiley, 2018)
This paper has the objectives of (a) comparing estimated willingness‐to‐pay (WTP) across three elicitation mechanisms (a Becker‐DeGroot‐Marschak [BDM] auction, a kth price auction, and a choice experiment [CE]) and (b) examining how these vary by participation fee. The product under consideration is kenkey made with nutritious maize, biofortified with vitamin A, which gives it a distinct orange color, in contrast to the white and yellow varieties that are traditionally consumed. We use an experiment consisting of 14 treatment arms, conducted in rural Ghana. Our estimation strategy explicitly accounts for the censored (typically at the market price) nature of the bids in the auctions, and the apparently lexicographic choices of several individuals in the CE. We find no evidence of economically meaningful (defined by the minimum currency unit of five pesewas) differences in WTP (although they may be statistically significant) across elicitation mechanisms, or by participation fee, a result that is in contrast to that found in much of the literature. A secondary finding is that the provision of nutrition information positively and significantly affects the marginal WTP for the new maize.